Habitat preferences and reproductive success for the threatened longhorn beetle Plagionotus detritus - Sundkvist, Lina (SLU/Dept. of Ecology, 2009)
Plagionotus detritus is a threatend longhorn beetle that only exists at one site in Sweden. It is saproxylic and depending on recently dead coarse oak wood for its larval development. Trees at Djurgården, Stockholm that have been colonized by Plagionotus detritus has been studied to find out the habitat preferences of the species and to see what affects the density of beetles in a tree. The bark of some trees and wood from the breeding project at Nordens Ark has also been studied to find out what affects the species reproductive success. The reproductive success was measured in two ways, the larval mortality and the size of the hatching holes.